The Proposed Model for Student’s Employability Enhancement in Clothing Design of Guangzhou Vocational Schools under Guangdong Province - Zhipin, Lyu; Jirarotephinyo, Nitwadee; Viphoouparakhot, Vorachai (APHEIT International Journal of Interdisciplinary Social Sciences and Technology, 2023)
The objectives of this research were to propose a model for students’ employability enhancement in clothing design of Guangzhou vocational schools under Guangdong province, the People’s Republic of China. The study adopted mixed methods research design. Population was faculty members of five public vocational schools in Guangdong Province. The key informants included three groups obtained by purposive sampling: 21 of administrators and teachers; 20 of current students and alumni; 5 of owner of companies hiring graduate students. The experts of 9 people were invited to a focus group discussion for comments, suggestions and confirmation of the model. The instruments used for collecting data from in-depth interview were interview questions and the collected data were analyzed by content analysis with frequency. The research results found: 1) Clothing design of Guangzhou vocational schools under Guangdong province under the current situation of students' employability both skills and the ability based on competencies were to be improved including knowledge, skills, attitude, characteristics and personal qualities; 2) The proposed model for students’ employability enhancement in clothing design of Guangzhou vocational schools is to focus on the policy reform in student development, cultivate smart strategy, create trust and harmonious learning environment between teachers and students.